2019
DOI: 10.1101/577833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liver X Receptor β Controls Hepatic Stellate Cell Activation via Hedgehog Signaling

Abstract: Liver X receptors (LXR) α and β serve important roles in cholesterol homeostasis, anti-inflammatory processes and the activation of hepatic stellate cells (HSCs). However, the development of therapies for liver fibrosis based on LXR agonists have been hampered due to side-effects such as liver steatosis. In this study, we demonstrated that HSCs expressed high levels of LXRβ, but not LXRα, and that overexpression of LXRβ suppressed fibrosis and HSC activation in a carbon tetrachloride (CCl4)-induced fibrosis mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…86 Moreover, the overexpression of LXRb has recently been shown to suppress fibrosis and HSC activation, without inducing steatosis, in a mouse model of carbon tetrachloride-induced fibrosis. 87 However, to further consider the potential therapeutic value of LXR agonists, the specific contribution of LXRa vs. LXRb needs to be addressed, considering the lipogenic properties of LXRa and the potential steatogenic side effects of non-selective LXRab-targeting molecules.…”
Section: Nuclear Receptors Lxrmentioning
confidence: 99%
“…86 Moreover, the overexpression of LXRb has recently been shown to suppress fibrosis and HSC activation, without inducing steatosis, in a mouse model of carbon tetrachloride-induced fibrosis. 87 However, to further consider the potential therapeutic value of LXR agonists, the specific contribution of LXRa vs. LXRb needs to be addressed, considering the lipogenic properties of LXRa and the potential steatogenic side effects of non-selective LXRab-targeting molecules.…”
Section: Nuclear Receptors Lxrmentioning
confidence: 99%
“…The filler tends to excessively flow and lead to a poor and incomplete joint. Zhong et al (2012) investigate joining of iron-nickel-cobalt alloy: Kovar® and glass using Cu-7.0Ni-9.0Sn-6.0P filler at brazing temperature 660 °C to 700 °C. Authors found initially the shear strength increase maximum to 11.6 MPa at 680 °C before drop at 700 °C [27].…”
Section: Resultsmentioning
confidence: 99%
“…Zhong et al (2012) investigate joining of iron-nickel-cobalt alloy: Kovar® and glass using Cu-7.0Ni-9.0Sn-6.0P filler at brazing temperature 660 °C to 700 °C. Authors found initially the shear strength increase maximum to 11.6 MPa at 680 °C before drop at 700 °C [27]. The finding is in agreement with the current study where further increasing brazing temperature will lead to reduce the shear strength.…”
Section: Resultsmentioning
confidence: 99%